Al-Adawiyah Karya K.H. Ahmad Sanusi dan Krisis Ekonomi Dunia (Malaise) Tahun 1929 - Kholis, Nurman (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2018)
This article tries to unpack a theme deals with syirik written in the manuscript of Al-Adawiyatu al-Syafiyatu fi Bayani Salati al-Hajati wa al-Istikharati wa Dafâ€™i al- Kurbat, a Sundanese text in the pegon scripts. This lithographic text was written by KH Ahmad Sanusi (1888-1950 M, a member of BPUKI (Committee for Preparatory Work for Indonesian Independence), established prior to the Indonesian independence in 1945. The text described at the time of being close toÂ independence proclaimation, there were criminal acts, particularly robbery cases growing significantly at that time. This social problem raised in society resulted in growing a phenomenon of which the people needed solution by consulting to dukun or visiting sacred places with hope of such lost articles would be back to the owners.Â In this case, KH Sanusi in his work recommended to the muslim not to do any syirik deeds, but it necessary to do pray sholat hajat or istikharah and increased their doa for it solution.Â The text of Adawiyah was written in 1348 H/1929 M which was coincidently happened with phenomenon of ecomic crises in the world. Keywords: al-Adawiyah, syirik, poverty, robbery, economic crisesÂ AbstrakArtikel ini mengungkap tema tentang syirik dalam naskah beraksara Pegon dan berbahasa Sunda yang berjudul Al-Adawiyatu al-Syafiyatu fi Bayani Salati al-Hajati wa al-Istikharati wa Dafâ€™i al-Kurbat. Naskah berbentuk litograf ini ditulis oleh K.H. Ahmad Sanusi (1888-1950 M), salah seÂorang anggota BPUPKI yang berdiri jelang kemerdekaan Indonesia tahun 1945. Dalam nasÂkah tersebut diinformasikan maraknya pencurian hingga banyak orang berdatangan ke tempat-tempat yang dikramatkan dan dukun untuk meÂngetahui barang-barang yang hilang. Untuk mengÂatasinya, K.H. Ahmad Sanusi memberikan solusi agar umat Islam tidak melakukan praktik-praktik syirik, namun melakukan salat hajat dan salat istikharah serta doa-doa untuk mengatasi keÂsulitan. Naskah al-Adawiyah ini ditulis pada tahun 1348 H/ 1929 M yang bersamaan dengan tahun terjadinya krisis ekonomi dunia (malaise). Rakyat miskin pun semakin bertambah, keÂrusuhan, pencurian, perampokan, juga marak di kota-kota maupun di desa-desa. Pada tahun 1929 ini selain terjadinya krisis ekonomi dunia juga merupakan awal munculnya istilah â€œtuyulâ€ di kalangan masyarakat Indonesia.Kata Kunci: al-Adawiyah, syirik, kemiskinan, pencurian, krisis ekonomi duniaÂ